The experience of trust in everyday life. (April 2022) - Weiss, Alexa; Burgmer, Pascal; Hofmann, Wilhelm
Abstract: In this contribution, we review current research on daily-life experiences of trust in diverse and naturally occurring social interactions ranging from close relationships to complete strangers. Experience-sampling methodology allows the joint examination of situational, relational, dispositional, motivational, and behavioral variables in their relation to trust. Thereby, these recent studies advance our understanding of how trust is shaped by important features of the social situation such as perceived conflict of interest. They elucidate how trust fluctuates in accordance with stable traits,  and how these traits interact with situational variables (e.g.,  social closeness to the target). Furthermore, trust connects social perceptions of trustees with trustors' prosocial tendencies. Highlights: Recent work studies trust in everyday life using experience-sampling methodology. Trust is shaped by the situation (e.g. conflict) and trustor–trustee relationship. Trait-level variables and the social context interact in predicting trust experiences. Trusting others is associated with prosocial behavioral intentions.